Retention of Atmospheric Particulate by Three Woody Ornamental Species in Santiago, Chile - Rubio-Campos, M; Ortiz-Calderon, C; Castro-Morales, S (Springer International Publishing, 2016)
It is traditionally accepted that urban vegetation contributes to improve air quality by intercepting and retaining the particulate matter. Although the mitigating role of plants has been recognized by several studies, the role of individual species is still poorly understood. This is particularly important in cities like Santiago (Chile), which has high levels of atmospheric particulate and also has high plant species diversity. In this study, we evaluated the retention of atmospheric particles by three widely distributed ornamental species (Nerium oleander, Pittosporum tobira, and Ligustrum lucidum) in Santiago. For this proposal, we took leaf samples in different sampling points across the city which vary in their concentration of atmospheric particulate. Samples were taken 12 and 16 days after a rainfall episode that washed the leaves of plants in the sampling sites. In the laboratory, leaves were washed to recover the surface retained particles that were collected to determine its mass gravimetrically. With this information, we estimated the foliar retention (mass of particulate matter retained in the foliar surface) and daily retention efficiency (mass of particulate matter retained in the foliar surface per day). We found that foliar retention and daily retention efficiency varied significantly between the studied species. The leaves of N. oleander retained 8.2 g m−2 of particulate matter on average, those of P. tobira 6.1 g m−2, and those of L. lucidum 3.9 g m−2; meanwhile, the daily retention efficiencies of particulate matter were 0.6, 0.4, and 0.3 g m−2 day−1 for N. oleander, P. tobira, and L. lucidum, respectively. These results suggest that the studied species retain atmospheric particulate matter differentially in Santiago. These results can be attributed to differences on leaf surface characteristics. The recognition of the most efficient species in the retention of the atmospheric particulate matter can help to decide which species can be used to improve the air quality in the city. © 2016, Springer International Publishing Switzerland.